The Influence of Democratic Leadership and Work Environment on Investment Performance Through Employee Motivation at the Investment and One-Stop Integrated Service Office (DPMPTSP) in Banten Province - Hikmatiar, Muhamad; Wiguna, Wahyu; Suparmoko, Muhammad (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Investment disparities between regions in Banten Province show significant differences. Cilegon City achieved the highest realization of IDR 34.696 trillion, while Serang City achieved the lowest at IDR 453.511 billion in 2024. This phenomenon indicates variations in the implementation of democratic leadership, work environment conditions, and employee motivation levels at the DPMPTSP, which influence investment performance. This study aims to analyze the influence of democratic leadership and the work environment on investment performance, both directly and through employee motivation as a mediating variable. The research location is the DPMPTSP of Banten Province, Cilegon City, and Serang City. The study used a quantitative method with a survey approach of 196 licensing and investment service employees. Questionnaires were collected through google form with scala Likert 1-5 and analyzed using PLS-SEM through SmartPLS 4.0 The results of the study indicate that seven hypotheses are accepted. Employee work motivation has the strongest influence on investment performance, followed by democratic leadership on motivation and work environment on motivation. Employee work motivation is proven to mediate the relationship between democratic leadership and work environment on investment performance. The integration of democratic leadership, a conducive work environment, and employee work motivation is the key to improving DPMPTSP investment performance. Practical implications are aimed at optimizing human resources and improving the work climate in public investment services.